l-Citrulline Metabolism in Mice Augments CD4+ T Cell Proliferation and Cytokine Production In Vitro, and Accumulation in the Mycobacteria-Infected Lung - Lange, Shannon M.; McKell, Melanie C.; Schmidt, Stephanie M.; Hossfeld, Austin P.; Chaturvedi, Vandana; Kinder, Jeremy M.; McAlees, Jaclyn W.; Lewkowich, Ian P.; Way, Sing Sing; Turner, Joanne; Qualls, Joseph E. (Frontiers in Immunology, 2017)
Activation, recruitment, and effector function of T lymphocytes are essential for control of mycobacterial infection. These processes are tightly regulated in T cells by the availability of L-arginine within the microenvironment. In turn, mycobacterial infection dampens T cell responsiveness through arginase induction in myeloid cells, promoting sequestration of L-arginine within the local milieu. Here we show T cells can replenish intracellular L-arginine through metabolism of L-citrulline to mediate inflammatory function, allowing anti-mycobacterial T cells to overcome arginase-mediated suppression. Furthermore, T cell L-citrulline metabolism is necessary for accumulation of CD4+ T cells at the site of infection, suggesting this metabolic pathway is involved during anti-mycobacterial T cell immunity in vivo. Together, these findings establish a contribution for L-arginine synthesis by T cells during mycobacterial infection, and implicate L-citrulline as a potential immuno-nutrient to modulate host immunity.